Platelet function and indices in Lithuanian men with dyslipidemia: associations with inflammatory biomarkers - Banys, Valdas; Andrejevaitė, Viktorija; Šapoka, Virginijus; Kučinskienė, Zita Aušrelė (Acta medica Lituanica, 2015)
Introduction. Platelet function, platelet volume indices, traditional markers of lipid metabolism, inflammatory markers and a novel biomarker, cyclophilin A (CyPA), are related as far as they have implications in pathogenesis of atherosclerosis. The purpose of this study was to evaluate interrelations among these factors, correlation between platelet function and inflammatory factors, also a function of CyPA. Materials and methods. 160 male patients with high risk of atherosclerosis and metabolic syndrome were included in the study. Inclusion criteria were as follows: disturbances in lipids profile, increased weight, smoking, acute or chronic stress, no previous or current acute cardiovascular disease (CVD), high risk and presence of stress confirmed by physician. CRP, vWF, fibrinogen, CyPA levels were measured. Platelet function was assessed by aggregation and flow cytometry. Results. Increasing number of risk factors gave statistically significant elevation in fibrinogen, thrombin receptors activating peptide, CRP, glucose, mean platelet volume (MPV), platelet large cell ratio, lipids and their ratios with extremely significant linearity. MPV correlated positively with CD42a (r = 0.605; p
Keywords: atherosclerosis; dyslipidemia; platelet indices; cyclophilin A; flow cytometry